Private Sector Solutions to Helping Smallholders Succeed : Social Enterprise Business Models in the Agriculture Sector - Tinsley, Elaine; Agapitova, Natalia (World Bank, Washington, DC, 2018)
Smallholder farmers in developing countries face tough challenges to their productivity, growth, and sustainability—including lack of access to affordable financial products, limited knowledge of high-quality inputs, low usage of technology and market data, and poor market links across the value chain. To close these gaps and help smallholder farmers thrive, social enterprises are implementing innovative solutions in the agriculture sector to serve them. Social enterprises are defined as private for-profit, nonprofit, or hybrid organizations that use business methods to advance their social mission. In the case of agriculture, social enterprises often address a particular pain point in the value chain, with the intention that the cost of their services or products will be recuperated by the benefits and income gains that smallholders will achieve. To serve such a “last mile” market, social enterprises will often develop a business model that is innovative, cost-effective, and provides strong value for money in providing quality services and products.The purpose of this book is to showcase the market-based solutions that have proven effective at supporting smallholders and to synthesize the experiences of social enterprises around the world. This book catalogues more than 100 social enterprises, categorized into 9 business models, that cut across the agriculture value chain.